Development of worksheet based on high-order thinking skills to improve high-order thinking skills of the students - Yennita, Yennita; Khasyyatillah, Isra; Gibran, Gibran; Irianti, Mitri (FKIP-Universitas Riau, 2018)
This research aimed to develop high order thinking skillsworkheet in momentum, impulse, and collision topic for senior high schoolThis type of research is Research and Development follow 4D models,includes : define, design, develop and disseminate. Data collectioninstruments used validation sheets for given to 5 validator, Aspects assessedinclude graphic, presentation, language, and the contents of workheet. Basedon the result of data analysis showed that all aspects got average score in therange of 3.4 to 4 with categories of very high. Thus, high order thinkingskills was valid. For the purposes of testing the worksheet is given on 68students. to measure the effectiveness of worksheet used Higher LevelThinking Ability Test that amounts to 12 items. Based on the result of dataanalysis indicate, There is difference of higher order thinking skill ofstudents who use HOTS worksheet than who are not use HOTS worksheet,where the average Higher Order Thinking Skill on students who use HOTSworksheet higher